Basics of commodity futures options markets with a focus on energy futures options markets - theoretical research - Mohammed Ali Ibrahim Al-Ameri; Maitham Rabie Hadi (Iraqi Journal for Administrative Sciences, 2025)
High flexibility of options helps participants of commodity futures options markets in formulate and implement a variant and wide trading strategies. But should be note here that some of these strategies are used for pure hedging, others are used for pure speculation, and others for both. Hedging strategies are different depending on identity of hedger itself, producer or consumer of spot commodity. Options are derived its value form its variant uses and success trading in options depends on select and implement a strategy which is help in achieving the required objectives. A risk size the participant likes to tolerance for potential return and a level of protection he or she likes to get should be taken in account because the insurance protection cost of option is increased with a level of protection it provides. All of these factors left to the holder or writer of option to estimate. Therefore this research is aimed to a knowledge and analytical discussing fundamentals of commodity futures options markets in general, and energy market in specific. This paper reached to number of conclusions, most important among them is the firms and institutions of developed countries still constitute a large percentage of commodity futures activity which is used for hedging or speculation. Also, direct and indirect using of futures exchange by the developing and Eastern Europe countries is somehow limited, so its participation is not active. Since a very small number of developing countries' companies and other institutions are members of the stock exchanges of developed countries. But this small number seems to be growing in.Commodity futures options market performs a number of functions aimed to serve the community, the most important of them are hedging, price discovery, and organized speculation. Also, the commodity futures options market has a positive impact on the spot market. Many of studies found that trading by these contracts did not increase volatility, but on the contrary it found a decrease in price risk and increase the trading volume, after introducing options for trading. This means that the launch of these contracts has increased the liquidity and stability of the spot market. This paper reached to number of recommendations, most important of them are the need to sensitize stakeholders and interested responsible parties and investors, individuals and institutions, by the importance of commodities futures options market which is trading with the latest and most effective systemic risk management tools in the world and draw their attention to the necessity and inevitability of possessing specialized knowledge and experience and depth in it.